(untitled) - Schroeder, Roger G. (New York, 2010)
Operations Management: Contemporary Concepts and Cases, is an ideal book for the instructor seeking a short text with cases. This book employs a cross-functional perspective, appealing to non-majors and practical for use in an MBA level course in operations management. The size and price of the book also make the text attractive for the cross-functional curriculum where students are required to purchase more than one text. The cases offer variety in length and rigor; and several are from Harvard and Darden. This mix makes the book appropriate for both undergraduates and MBA students.
Keywords: Production managemen,Quản lý sản xuất